Culture, Society and Economic Theory - William A. Jackson (Review of Political Economy, 1993)
Ever since the beginnings of classical political economy in the early nineteenth century, economics has faced culturally based criticism from a long line of literary authors. This paper argues that the old literary criticisms are still relevant and can provide useful guidelines for economic theory. Their great merit is that they rest on the original definition of culture as a process, which avoids a static separation of structure and agency. The same principle underlies some recent work in social theory and could be an important unifying theme for non-neoclassical economics. A culturally informed institutional economics could build upon much that is valuable in existing institutional, post Keynesian and Marxian approaches. It would also be equipped to address cultural and interpretative questions beyond the ken of mainstream economics.
Keywords: A12; A13; B41; B50; Z10; 330; culture; structure; agency; economic theory; pluralism; interpretative methods